2005
DOI: 10.5432/ijshs.3.35
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characteristics of Distance Running on Downhill Slope

Abstract: The purpose of this study was to investigate kinetic characteristics such as ground reaction forces (GRFs) and joint torques of the lower limb joints in downhill running for distance runners on overground. Six male distance runners were asked to run at three running speeds (3.3, 4.2, and 5.0 m/s) on the slopes of different grades (0, -3.2, -6.4, and -9.1 %) in which two force platforms were mounted. A two dimensional link model was used to calculate joint torques and joint powers of the lower limb joints. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
7
11
1
Order By: Relevance
“…Similarly, the increase in hip power generation during early stance in incline running indicates an increase in the rate of concentric loading. These results corroborate the findings of Yokozawa et al 27 with regard to power absorption during decline running as well as those of Swanson and Caldwell 28 and Roberts and Belliveau 29 with regard to increased hip power generation with incline running, albeit on a lower-grade slope. It should be noted that we held speed constant to standardize findings.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the increase in hip power generation during early stance in incline running indicates an increase in the rate of concentric loading. These results corroborate the findings of Yokozawa et al 27 with regard to power absorption during decline running as well as those of Swanson and Caldwell 28 and Roberts and Belliveau 29 with regard to increased hip power generation with incline running, albeit on a lower-grade slope. It should be noted that we held speed constant to standardize findings.…”
Section: Discussionsupporting
confidence: 91%
“…Increased ILP activity during UR would play an important role in faster and greater hip flexion in FRP. In SRP, greater muscle torques by GMAX, HAMS, and ADD during UR at the high speed increased the net hip extension torque and knee flexion torque, which would subsequently contribute to rapid backward swing of the leg before foot contact (Yokozawa et al, 2003). Contrary to our expectation, the knee extension torque by VAS in SP was significantly smaller during UR at all the speeds.…”
Section: Muscle Torque Of the Lower Limbcontrasting
confidence: 74%
“…Heise et al (1996) reported that economical runners exhibited a greater amount of coactivation of RF and HAMS during SP when compared with noneconomical runners. In addition, the forward lean of the trunk is greater during UR throughout one running cycle (Paradisis and Cooke, 2001;Yokozawa et al, 2003). This indicates that the increased coactivation of RF and HAMS during UR in the present study would help to maintain the trunk in a forward-leaning position.…”
Section: Article In Pressmentioning
confidence: 61%
See 2 more Smart Citations